Educational-Spiritual Learning Model Based on Geguritan Sucita Subudi (Innovation in Learning Balinese Literature Based on Local Wisdom) - Putra, Made Susila; Putu Agita Hary Devianti (Universitas Pendidikan Ganesha, 2025)
Balinese Language learning in formal schools still faces serious challenges, particularly in terms of low student engagement and the suboptimal use of local literature as a teaching medium. One proposed solution is the development of an educational-spiritual learning model based on Geguritan Sucita Subudi, which is rich in moral and spiritual values. This study aims to analyze the educational-spiritual learning model based on Geguritan Sucita Subudi. The research adopts a qualitative approach using the Research and Development (R&D) method by Borg & Gall, which includes stages such as field study, model design, expert validation, limited implementation, and evaluation. Data were collected through observation, interviews, and documentation. The data analysis technique employed qualitative analysis with data triangulation. The findings show that this model enhances students’ understanding of the content of geguritan, fosters affective and spiritual engagement, and strengthens character education rooted in local culture. The implementation of this model also demonstrates a positive impact on preserving the values of Balinese literature within the context of formal education. The implications of this study make a significant contribution to strategies for strengthening a curriculum based on local wisdom and support the implementation of the Freedom to Learn (Merdeka Belajar) policy and the Pancasila Student Profile in a contextual and meaningful way.